Polyaryl ether ketone resin composition, fiber-reinforced resin substrate and molded article
The polyaryletherketone resin composition, enhanced with a transition metal compound and polyvalent amine, addresses thermal and mechanical property challenges, offering superior stability and bonding strength in fiber-reinforced materials.
Patent Information
- Application Number
- JP2020549079
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-20
- Filing Date
- 2020-09-11
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2040-09-11
AI Technical Summary
Existing polyaryletherketone resin compositions face challenges in maintaining thermal stability and mechanical properties under harsh environments, with previous methods either failing to provide sufficient thermal stability or compromising mechanical properties.
A polyaryletherketone resin composition is formulated by incorporating a transition metal compound, specifically a Group 10 element, within a specific content range, along with a polyvalent amine and fibrous filler, to enhance thermal stability and mechanical properties.
The composition achieves excellent thermal stability and mechanical properties, with improved resistance to oxidative deterioration and enhanced bonding strength in fiber-reinforced resin base materials.
Smart Images

Figure 0007619043000007 
Figure 0007619043000008 
Figure 0007619043000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyaryl ether ketone resin composition, a fiber-reinforced resin substrate, and a molded article. [Background technology]
[0002] Polyaryletherketone is one of the representative super engineering plastics with excellent properties such as heat resistance, chemical resistance, flame retardancy, sliding properties, and friction and wear properties. Due to its excellent physical properties, polyaryletherketone is widely used in machine parts, automobile parts, aviation parts, electrical and electronic parts, etc. Demand for polyaryletherketone is expanding in fields with extremely harsh usage conditions and as a metal replacement material, and there is a demand for improved thermal stability and mechanical properties.
[0003] As a means for improving the thermal stability of polyaryletherketone, Patent Document 1 discloses that a polyaryletherketone resin composition having high thermal stability can be obtained by blending a phosphate with a polyaryletherketone resin. Patent Document 2 discloses that a polyaryletherketone resin composition having high thermal stability can be obtained by incorporating an organic compound having a base constant of 2 to 12 and a boiling point of more than 300° C. in a polyaryletherketone resin.
[0004] As a means for improving the mechanical properties of a polyaryl ether ketone resin, Patent Document 3 discloses that a polyaryl ether ketone resin composition having excellent mechanical properties can be obtained by blending a polyetherimide resin and fine talc with a polyaryl ether ketone resin.
[0005] Furthermore, as a means for improving the thermal stability of thermoplastic resins, Patent Document 4 describes that blending a polyphenylene ether resin and a polyamide resin with a metal halide or metal carboxylate of a metal selected from copper, nickel, tin and cerium results in excellent thermal stability. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Special Publication No. 2018-520257 [Patent Document 2] Japanese Patent Application Publication No. 4-224862 [Patent Document 3] JP 2007-197715 A [Patent Document 4] Japanese Patent Application Publication No. 1-163262 Summary of the Invention [Problem to be solved by the invention]
[0007] The methods proposed in Patent Documents 1 and 2 provide polyaryl ether ketone resin compositions with high thermal stability, but have problems with thermal stability under harsher environments. The method proposed in Patent Document 3 provides an improvement in mechanical properties, but has problems with thermal stability. The method proposed in Patent Document 4 does not provide a sufficient improvement in thermal stability for polyaryl ether ketone resins.
[0008] An object of the present invention is to solve the above-mentioned problems of the conventional techniques and to provide a polyaryl ketone resin composition, a fiber-reinforced resin substrate, and a molded article thereof, which have excellent thermal stability and mechanical properties. [Means for solving the problem]
[0009] The present invention was achieved as a result of studies aimed at solving the problems in the prior art described above, and has the following configuration. [1] A polyaryl ether ketone resin composition comprising (A) a polyaryl ether ketone and (B) a transition metal compound, the polyaryl ether ketone resin composition having a transition metal content of 0.001 parts by mass or more and 4 parts by mass or less per 100 parts by mass of the (A) polyaryl ether ketone. [2] The polyaryl ether ketone resin composition according to [1], wherein the transition metal compound (B) is a compound of an element of Group 10 of the periodic table. [3] The polyaryl ether ketone resin composition according to [1] or [2], wherein the complete decomposition temperature of the transition metal compound (B) is equal to or lower than the melting point of the polyaryl ether ketone (A). [4] The polyaryl ether ketone resin composition according to any one of [1] to [3], wherein the complete decomposition temperature of the transition metal compound (B) is 25° C. or higher and 300° C. or lower. [5] The polyaryl ether ketone resin composition according to any one of [1] to [4], comprising (D) 0.01 part by mass or more and 5 parts by mass or less of a polyamine per 100 parts by mass of the polyaryl ether ketone (A). [6] The polyaryl ether ketone resin composition according to any one of [1] to [5], comprising (E) 10 parts by mass or more and 400 parts by mass or less of a fibrous filler per 100 parts by mass of the polyaryl ether ketone (A). [7] A fiber-reinforced resin substrate obtained by impregnating a reinforcing fiber substrate having a continuous (E) fibrous filler or a discontinuous (E) fibrous filler dispersed therein with the polyaryl ether ketone resin composition according to any one of [1] to [5]. [8] A molded article obtained by molding the polyaryl ether ketone resin composition according to any one of [1] to [6] or the fiber-reinforced resin substrate according to [7]. Effect of the Invention
[0010] According to the present invention, it is possible to obtain a polyaryl ether ketone resin composition, a fiber-reinforced resin substrate, and a molded article thereof, which have excellent thermal stability and mechanical properties. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1B is a diagram showing the results of thermogravimetric analysis of nickel (II) formate dihydrate under specified conditions. [Diagram 2] FIG. 2 is a schematic diagram showing fiber-reinforced resin molded bodies welded together. [Diagram 3] FIG. 2 is a schematic diagram of a molded article prepared for evaluating formability used in the examples of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The polyaryl ether ketone resin composition of the present invention contains (A) a polyaryl ether ketone and (B) a transition metal compound.
[0013] <(A) Polyaryl ether ketone> The polyarylene ether ketone (A) used in the present invention is not particularly limited as long as it is a thermoplastic resin having a repeating unit in which an aryl group is bonded via an ether group and a ketone group, but is preferably a polymer having units of the following general formula (Ia) and general formula (Ib).
[0014] [ka]
[0015] Here, Ar 1 and Ar 2 Each of Ar represents an arylene group. 1 and Ar 2 may be the same or different. 1 and Ar 2 are preferably each independently one or more arylene groups selected from the group consisting of 1,3-phenylene, 1,4-phenylene, 4,4'-biphenylene, 1,4-bis(4-phenoxybenzoyl)phenylene, 1,4-naphthylene, 1,5-naphthylene, 2,6-naphthylene, and anthracenylene. X represents an electron-withdrawing group. X is preferably one or more groups selected from the group consisting of a carbonyl group and a sulfonyl group. Y is one or more groups selected from the group consisting of an oxygen atom, a sulfur atom, and an alkylene group. Y is preferably one or more groups selected from the group consisting of -CH2-, isopropylidene, and hexafluoroisopropylidene.
[0016] In these structural units, preferably at least 50 mol % of X is a carbonyl group, more preferably at least 70 mol % of X. Furthermore, preferably at least 50 mol % of Y is an oxygen atom, more preferably at least 70 mol % of Y is an oxygen atom.
[0017] Examples of polyaryl ether ketones include polyether ether ketones having a structural unit of the following formula (II) and / or a structural unit of the following formula (III), polyether ketones having a structural unit of the following formula (IV), polyether ketone ketones having a structural unit of the following formula (V) and / or a structural unit of the following formula (VI), polyether ether ketone ketones having a structural unit of the following formula (VII), polyether ketone ether ketone ketones having a structural unit of the following formula (VIII), etc. These may be used alone or in combination of two or more kinds.
[0018] [ka]
[0019] The polyaryl ether ketone is not particularly limited, but for example, commercially available products such as "Vestakeep (registered trademark)" manufactured by Daicel-Evonik Ltd., "VICTREX (registered trademark)" manufactured by Victrex Japan Ltd., "KEPSTAN (registered trademark)" manufactured by Arkema K.K., and "AvaSpire (registered trademark)", "KetaSpire (registered trademark)" and "NovaSpire (registered trademark)" manufactured by Solvay Specialty Polymers Japan Ltd. can be obtained and used.
[0020] <(B) Transition metal compound> The transition metal compound used in the present invention is not particularly limited as long as it is a compound of a transition metal.
[0021] Unlike typical elements, transition metals have a tendency to easily form coordinate bonds because their d orbitals or f orbitals are not closed and they can have stable unpaired electrons. The more easily a transition metal can form a coordinate bond, the more preferable it is because a polyaryl ether ketone resin composition having excellent thermal stability and mechanical properties can be obtained. As transition metals that easily form coordinate bonds, those with a smaller ionic radius are preferable because they are more easily coordinated. Specific examples of transition metals with a small ionic radius include ruthenium, rhodium, technetium, molybdenum, iridium, osmium, rhenium, tungsten, tantalum, hafnium, zirconium, zinc, copper, nickel, cobalt, iron, chromium, and manganese.
[0022] The reason why the polyaryletherketone resin composition of the present invention exhibits excellent thermal stability and mechanical properties is not necessarily clear, but can be assumed as follows. When (A) polyaryletherketone is heated in the presence of oxygen at a temperature equal to or higher than the melting point, active oxygen radicals extract protons on the aromatic rings to generate phenyl radicals, and the phenyl radicals are the starting point for excessive crosslinking reactions. This leads to poor thermal stability and poor mechanical properties. It can be assumed that by coordinating a transition metal with high coordination bond ability on the aromatic rings, the extraction of protons can be suppressed, and crosslinking can be suppressed, that is, a polyaryletherketone resin composition with excellent thermal stability and mechanical properties can be obtained. It can also be assumed that by coordinating a transition metal on the aromatic rings of (A) polyaryletherketone, molecular chains can be linked by coordination bonds to obtain a moderately crosslinked polyaryletherketone, and mechanical properties can be further improved.
[0023] On the other hand, when a polyaryl ether ketone resin composition contains an alkali metal compound (C) with a similar metal content instead of a transition metal compound (B) with a transition metal content of 0.001 to 4 parts by mass per 100 parts by mass of polyaryl ether ketone (A), the coordination bond ability is weak and the compound cannot be coordinated on the aromatic ring of the polyaryl ether ketone, so that a polyaryl ether ketone resin composition with excellent thermal stability and mechanical properties cannot be obtained. Here, examples of such an alkali metal compound (C) include salts of alkali metals selected from lithium, sodium, potassium, rubidium, cesium, and francium. Specific examples include salts such as carboxylates, halides, phosphates, carbonates, hydroxides, oxides, sulfides, acetylacetone complexes, and alkoxides of alkali metals.
[0024] In the polyaryl ether ketone resin composition of the present invention, the (B) transition metal compound is preferably a compound of a Group 10 element of the periodic table. This is because Group 10 elements of the periodic table are rich in electrons and therefore tend to undergo oxidative addition, i.e., coordinate bonding. Among these, nickel is the most preferred because of its small ionic radius.
[0025] (B) Examples of the transition metal compound include metal salts such as carboxylates, halides, carbonates, hydroxides, oxides, sulfides, acetylacetone complexes, and alkoxides of the transition metals. Examples of the carboxylic acid include formic acid, acetic acid, propionic acid, butyric acid, stearic acid, lactic acid, oleic acid, benzoic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, and adipic acid. Examples of the alkoxide include butoxide, propoxide, ethoxide, and methoxide. From the viewpoint of preferring a transition metal compound with a low complete decomposition temperature, carboxylates are preferred, and among the carboxylates, formic acid and acetic acid are more preferred, and formic acid is even more preferred.
[0026] In the polyaryletherketone resin composition of the present invention, the complete decomposition temperature of the transition metal compound (B) is preferably equal to or lower than the melting point of the polyaryletherketone (A). When the complete decomposition temperature of the transition metal compound (B) is equal to or lower than the melting point of the polyaryletherketone (A), the transition metal is reduced to a zero-valent transition metal by heating the polyaryletherketone resin composition of the present invention at a temperature equal to or higher than the melting point of the polyaryletherketone (A). This zero-valent transition metal is preferred because it has high activity and is likely to form coordinate bonds by oxidative addition. The complete decomposition temperature of the transition metal compound (B) is more preferably equal to or lower than the melting point of the polyaryletherketone (A) minus 30°C, and even more preferably equal to or lower than the melting point of the polyaryletherketone (A) minus 70°C.
[0027] In the polyaryl ether ketone resin composition of the present invention, the complete decomposition temperature of the (B) transition metal compound is preferably 25°C or higher and 300°C or lower. If the complete decomposition temperature of the (B) transition metal compound is 25°C or higher, it is unlikely to be oxidized and therefore unlikely to become an inactive oxidized transition metal. The complete decomposition temperature of the (B) transition metal compound is preferably 100°C or higher, more preferably 150°C or higher. In addition, if the complete decomposition temperature of the (B) transition metal compound is 300°C or lower, the transition metal is likely to be reduced when the polyaryl ether ketone resin composition is heated, and coordinate bonds due to oxidative addition are likely to occur, which is preferable. The complete decomposition temperature of the (B) transition metal compound is more preferably 270°C or lower.
[0028] In the polyaryl ether ketone resin composition of the present invention, the complete decomposition temperature of the transition metal compound (B) is equal to or lower than the melting point of the polyaryl ether ketone (A), and is more preferably 25°C or higher and 300°C or lower.
[0029] The complete decomposition temperature is the temperature at which the compound components other than the transition metal in the transition metal compound are substantially almost completely decomposed or separated from the transition metal. This temperature is measured by weighing the transition metal compound in a container and measuring the mass change while heating at a constant rate in an inert gas atmosphere using a thermogravimetric analyzer. The thermal reduction rate is measured while heating the transition metal compound in a nitrogen atmosphere, and the complete decomposition temperature is defined as the temperature at which the mass reduction does not proceed any further. The temperature at which the mass reduction rate reaches 90% of the mass of the compound components other than the transition metal in the transition metal compound is used to determine the complete decomposition temperature.
[0030] The melting point of the (A) polyaryl ether ketone can be measured by differential scanning calorimetry.
[0031] In the polyaryl ether ketone resin composition of the present invention, the transition metal content is 0.001 to 4 parts by mass relative to 100 parts by mass of (A) polyaryl ether ketone. The transition metal content is preferably 0.01 to 2 parts by mass, more preferably 0.1 to 1 part by mass. If the transition metal content is less than 0.001 parts by mass, it is difficult to obtain an excellent thermal stabilization effect. If the transition metal content is more than 4 parts by mass, aggregation of the (B) transition metal compound is likely to occur, making it impossible to obtain excellent thermal stabilization effect and mechanical properties.
[0032] The total content of (A) polyaryl ether ketone and transition metal in the polyaryl ether ketone resin composition of the present invention is preferably 20% by mass or more and 100% by mass or less, and more preferably 30% by mass or more and 100% by mass or less.
[0033] The transition metal content in the polyaryl ether ketone resin composition of the present invention is quantified by incinerating the polyaryl ether ketone resin composition, thermally decomposing the incinerated product with sulfuric acid or hydrofluoric acid, and then dissolving the resultant in dilute sulfuric acid or aqua regia to obtain a constant volume solution, which is then analyzed using an ICP mass spectrometer and an ICP atomic emission spectrometer.
[0034] The content of polyaryl ether ketone (A) in the polyaryl ether ketone resin composition can be measured as follows: The polyaryl ether ketone resin composition is dissolved in a solvent in which polyaryl ether ketone (A) dissolves, such as sulfuric acid, and the insoluble matter is filtered off, and the soluble matter is precipitated and recovered in a poor solvent. The content can be measured by qualitative and quantitative analysis such as high performance liquid chromatography using, for example, a mixed solvent of chloroform and dichloroacetic acid or a mixed solvent of chlorophenol and halogenated benzenes as a solvent in which the recovered matter dissolves.
[0035] <(D) Polyamine> The polyaryl ether ketone resin composition of the present invention preferably contains (D) a polyamine. By containing (D) a polyamine, the mechanical properties can be further improved.
[0036] The polyamine (D) is not particularly limited as long as it has two or more amino groups in one molecule, but from the viewpoint of maintaining thermal stability and mechanical properties, the number of amino groups is preferably 2 to 10. In addition, since a polyamine that does not volatilize when the polyaryletherketone resin composition is heated at a temperature equal to or higher than the melting point of the polyaryletherketone (A), a polyamine having a vapor pressure of less than 1 atmosphere at 300°C is preferred. A polyamine having a vapor pressure of less than 1 atmosphere at 325°C, and more preferably at 350°C, is preferred. When the polyaryletherketone resin composition of the present invention is melt-mixed and molded, how much of the polyamine (D) is retained in the polyaryletherketone resin composition depends on its volatility. A polyamine having a vapor pressure of more than 1 atmosphere at 300°C tends to be too volatile and not retained sufficiently in the resin composition. Depending on the type of polyamine, it may sublimate and not show a true boiling point, so the limit of volatility is expressed as the limit of vapor pressure rather than the limit of boiling point. Additionally, for compounds that exhibit a boiling point, the limit of volatility can be expressed as a boiling point above 300°C at 1 atmosphere.
[0037] Preferred (D) polyvalent amines include, for example, aliphatic amines such as 1,10-diaminodecane, 1,11-diaminoundecane, 1,12-diaminododecane, 1,13-diaminotridecane, 1,14-diaminotetradecane, 1,15-diaminopentadecane, 1,16-diaminohexadecane, 1,17-diaminoheptadecane, and 1,18-diaminooctadecane; 2,2'-biphenyldiamine, 4,4'-biphenyldiamine, 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfone, 4,4' -diaminodiphenylsulfone, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 9,9-bis(4-aminophenyl)fluorene, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminobenzophenone, 3,3'-diaminobenzophenone, meta-tolidine, ortho-tolidine, 3,3'-diaminobenzidine, and other aromatic amine compounds. Among these, aromatic amine compounds are preferred in terms of low volatility, and polyvalent amines having a diphenyl ether skeleton are more preferred in terms of excellent affinity with (A) polyaryl ether ketone, with 4,4'-diaminodiphenyl ether being even more preferred.
[0038] By containing a polyvalent amine (D) in the polyaryl ether ketone resin composition of the present invention, the amino groups of the polyvalent amine (D) are bonded to the ketone groups of the polyaryl ether ketone (A) through a nucleophilic addition reaction, thereby forming a moderate crosslinked structure and improving the mechanical properties.
[0039] The polyaryl ether ketone resin composition of the present invention preferably contains 0.01 to 5 parts by mass of the polyamine (D) relative to 100 parts by mass of the polyaryl ether ketone (A). If the amount is 0.01 part by mass or more, the mechanical properties of the polyaryl ether ketone resin composition can be further improved. If the amount is 5 parts by mass or less, it is easy to suppress a decrease in toughness due to excessive crosslinking.
[0040] The method for measuring the content of (D) polyamine can involve filtering the polyaryl ether ketone resin composition using a solvent in which (A) polyaryl ether ketone and polyamine are soluble, such as a mixed solvent of chloroform and dichloroacetic acid or a mixed solvent of chlorophenol and a halogenated benzene, filtering off the insoluble matter, and then measuring the content of the (D) polyamine by qualitative and quantitative analysis such as high performance liquid chromatography.
[0041] <(E) Fibrous filler> The polyaryl ether ketone resin composition of the present invention preferably further comprises (E) a fibrous filler, which can further improve the mechanical properties.
[0042] (E) Examples of fibrous fillers include glass fibers, carbon fibers, aramid fibers, polyamide fibers, polyester fibers, vinylon fibers, cotton, hemp fibers, kenaf fibers, bamboo fibers, rayon, steel fibers, aluminum fibers, etc. The shape of these fibrous fillers includes continuous fibers, short fibers such as chopped strands, and whiskers.
[0043] The polyaryl ether ketone resin composition of the present invention preferably contains 10 parts by mass or more and 400 parts by mass or less of the fibrous filler (E) relative to 100 parts by mass of the polyaryl ether ketone (A). If it is 10 parts by mass or more, the mechanical properties of the polyaryl ether ketone resin composition can be further improved. Also, if it is 400 parts by mass or less, the moldability is less likely to decrease.
[0044] The (E) fibrous filler content can be measured as follows. The polyaryl ether ketone resin composition is filtered using a solvent in which (A) polyaryl ether ketone and (D) polyamine dissolve, such as a mixed solvent of chloroform and dichloroacetic acid or a mixed solvent of chlorophenol and halogenated benzenes, to remove insoluble matter, and (E) fibrous filler and (B) transition metal compound are recovered as the filtrate. The fibrous filler is further removed using a solvent in which (B) transition metal compound dissolves, and the mass is measured after washing.
[0045] <Fiber-reinforced resin substrates, molded products> The fiber-reinforced resin substrate of the present invention is obtained by impregnating a continuous (E) fibrous filler or a reinforcing fiber substrate in which a discontinuous (E) fibrous filler is dispersed, with the polyaryl ether ketone resin composition of the present invention.
[0046] That is, the fiber-reinforced resin substrate of the present invention can be exemplified by the following two embodiments. The first embodiment is a fiber-reinforced resin substrate obtained by impregnating a continuous (E) fibrous filler with a polyaryletherketone resin composition. The second embodiment is a fiber-reinforced resin substrate obtained by impregnating a reinforcing fiber substrate having a discontinuous (E) fibrous filler dispersed therein with a polyaryletherketone resin composition.
[0047] The continuous (E) fibrous filler in the first embodiment refers to a fiber-reinforced resin substrate in which the reinforcing fibers are uninterrupted. Examples of the form and arrangement of the continuous (E) fibrous filler include those aligned in one direction, woven fabric (cloth), knitted fabric, braided cord, tow, etc. Among them, it is preferable that the continuous (E) fibrous filler is aligned in one direction, since this can efficiently improve the mechanical properties in a specific direction.
[0048] The reinforcing fiber substrate in which the discontinuous (E) fibrous filler is dispersed in the second embodiment refers to a mat-like structure in which the fibrous filler is cut and dispersed in the fiber-reinforced resin substrate. The reinforcing fiber substrate can be obtained by any method, such as a wet method in which fibers are dispersed in a solution and then produced in a sheet form, or a dry method using a carding device or an airlaid device. From the viewpoint of productivity, a dry method using a carding device or an airlaid device is preferred. The number average fiber length of the discontinuous (E) fibrous filler in the reinforcing fiber substrate is preferably 3 to 100 mm. If the number average fiber length of the discontinuous fibers is 3 mm or more, the reinforcing effect of the discontinuous fibers is sufficiently exhibited, and the mechanical strength of the obtained fiber-reinforced resin substrate can be further improved. 5 mm or more is preferred. On the other hand, if the number average fiber length of the discontinuous fibers is 100 mm or less, the flowability during molding can be further improved. The number average fiber length of the discontinuous fibers is more preferably 50 mm or less, and even more preferably 30 mm or less.
[0049] The number average fiber length of the discontinuous fibers can be determined by the following method. First, a sample of 100 mm x 100 mm is cut out from the fiber-reinforced resin substrate, and the cut sample is heated in an electric furnace at 600°C for 1.5 hours to burn off the matrix resin. 400 discontinuous reinforcing fiber bundles are randomly sampled from the fiber-reinforced resin substrate thus obtained. The fiber length of the discontinuous reinforcing fiber bundles thus sampled is measured in 1 mm increments using a vernier caliper, and the number average fiber length (Ln) can be calculated by the following formula.
[0050] Ln=ΣLi / 400 (Li: measured fiber length (i = 1, 2, 3, 400) (unit: mm)).
[0051] The number average fiber length of the discontinuous fibers can be adjusted to the above range by cutting the fibers to a desired length during the production of the reinforcing fiber substrate. There is no particular restriction on the orientation of the discontinuous fiber mat, but from the viewpoint of moldability, it is preferable that the fibers are dispersed isotropically.
[0052] In the first embodiment, the method of impregnating the continuous (E) fibrous filler with the polyaryletherketone resin composition includes, for example, a film method in which a film-shaped polyaryletherketone resin composition is melted and pressurized to impregnate a reinforcing fiber bundle with the polyaryletherketone resin composition, a comingle method in which a fibrous polyaryletherketone resin composition is mixed with a reinforcing fiber bundle, and then the fibrous polyaryletherketone resin composition is melted and pressurized to impregnate the reinforcing fiber bundle with the polyaryletherketone resin composition, a powder method in which a powdered polyaryletherketone resin composition is dispersed in the gaps between the fibers in the reinforcing fiber bundle, and then the powdered polyaryletherketone resin composition is melted and pressurized to impregnate the reinforcing fiber bundle, and a pultrusion method in which a reinforcing fiber bundle is immersed in a molten polyaryletherketone resin composition and pressurized to impregnate the reinforcing fiber bundle with the polyaryletherketone resin composition. The pultrusion method is preferred because it can produce a wide variety of fiber-reinforced resin substrates with various thicknesses and fiber volume contents.
[0053] In the second embodiment, examples of the method for impregnating the reinforcing fiber substrate having the discontinuous (E) fibrous filler dispersed therein with the polyaryletherketone resin composition include a method in which the polyaryletherketone resin composition is supplied by an extruder to impregnate the reinforcing fiber substrate, a method in which a powdered polyaryletherketone resin composition is dispersed in a fiber layer of a reinforcing fiber substrate and melted, a method in which the polyaryletherketone resin composition is made into a film and laminated with the reinforcing fiber substrate, a method in which the polyaryletherketone resin composition is dissolved in a solvent and impregnated into the reinforcing fiber substrate in the form of a solution, and then the solvent is volatilized, a method in which the polyaryletherketone resin composition is made into a fiber to form a mixed yarn with discontinuous fibers, and a method in which the composition is laminated using a melt-blown nonwoven fabric.
[0054] In addition, the fiber reinforced resin substrate of the present invention can be selected according to the desired impregnation property depending on the usage and purpose. For example, prepreg with higher impregnation property, semi-preg with half impregnation, fabric with low impregnation property, etc. are included. In general, the more impregnated the molding material, the more preferable it is because a molded product with excellent mechanical properties can be obtained by molding for a short time.
[0055] The fiber-reinforced resin substrate impregnated with the polyaryl ether ketone resin composition of the present invention has excellent thermal stability, and therefore has excellent bonding strength when the fiber-reinforced resin substrates are bonded together. This is thought to be because the fiber-reinforced resin substrates are heated in an oxygen atmosphere when bonded together, and oxidation deterioration on the substrate surface can be suppressed, resulting in excellent bonding strength.
[0056] The molded article of the present invention is obtained by molding the polyaryl ether ketone resin composition of the present invention or the fiber-reinforced resin substrate of the present invention.
[0057] <Method of producing polyaryl ether ketone resin composition> The method for producing the polyaryl ether ketone resin composition of the present invention is not particularly limited, but a preferred example thereof is a method in which (A) polyaryl ether ketone and (B) transition metal compound, and optionally (D) polyamine, are dry blended and fed from a main feeder of an extruder, and optionally (E) fibrous filler is fed from a side feeder of the extruder, and then melt-kneaded at a temperature equal to or higher than the melting point of (A) polyaryl ether ketone.
[0058] <Method for molding polyaryl ether ketone resin composition> The method for molding the polyaryl ether ketone resin composition of the present invention is not particularly limited, and examples thereof include injection molding, extrusion molding, compression molding, etc. Molded articles such as molded products, sheets, and films can be obtained by such molding methods.
[0059] In addition, examples of a method for molding a fiber-reinforced resin substrate impregnated with a polyaryl ether ketone resin composition include a press molding method in which a material obtained by laminating fiber-reinforced resin substrates in any configuration is heated and pressurized, an autoclave molding method in which the material is placed in an autoclave and heated and pressurized, a bagging molding method in which the material is wrapped in a film or the like, the inside is reduced pressure, and the material is heated in an oven while being pressurized at atmospheric pressure, and a wrapping tape method in which a tape is wrapped around the material under tension and the material is heated in an oven.
[0060] As the press molding method, a hot press method in which a fiber-reinforced resin substrate is placed in a mold in advance, pressurized and heated while the mold is closed, and then the mold is cooled to cool the fiber-reinforced resin substrate while the mold is still closed, to obtain a molded product, or stamping molding, a method in which a fiber-reinforced resin substrate is heated in advance to a temperature equal to or higher than the melting temperature of the thermoplastic resin by a heating device such as a far-infrared heater, a heating plate, a high-temperature oven, or a dielectric heater, and the thermoplastic resin is placed in a melted and softened state on a mold that will become the lower surface of the molding die, then the mold is closed to close the mold, and thereafter the mold is pressurized and cooled, can be used. There are no particular limitations on the press molding method, but stamping molding is preferable from the viewpoint of accelerating the molding cycle and increasing productivity.
[0061] <Other ingredients> If desired, the polyaryl ether ketone resin composition of the present invention may also contain added thermoplastic resins other than polyaryl ether ketone, inorganic fillers other than fibrous fillers such as titanium oxide and calcium carbonate, antioxidants, heat stabilizers, ultraviolet absorbers, colorants, and the like.
[0062] Examples of thermoplastic resins other than polyaryletherketone include polycarbonate resins, polyarylate resins, ABS resins, poly(meth)acrylate resins, (meth)acrylate polyethylene resins, polypropylene resins, syndiotactic polystyrene resins, and other polyolefin resins, polyvinyl alcohol resins, polyvinylidene chloride resins, polyester resins, polyamide resins, polyacetal resins, polyimide resins, polytetrafluoroethylene resins, polysulfone resins, polyarylene sulfide resins, and polyphenylene ether resins, and may be used alone or in combination. Among these, from the viewpoint of not impairing the heat resistance of polyaryletherketone, polyimide resins, polytetrafluoroethylene resins, polysulfone resins, polyarylene sulfide resins, and polyphenylene ether resins that are excellent in heat resistance are preferred, and polyimide resins and polysulfone resins that are excellent in compatibility with polyaryletherketone are more preferred from the viewpoint of improving mechanical properties.
[0063] A polyimide resin is a polymer having an imide bond in the repeating unit. In the present invention, polyetherimide resins having an ether bond in the repeating unit other than the imide bond and polyamideimide resins having an amide bond are also classified as polyimide resins.
[0064] Polysulfone resins are polymers that contain sulfonyl groups in their repeating units. Polyethersulfone and polyphenylsulfone are also classified as polysulfone resins.
[0065] <Application examples of molded products> Molded articles obtained from the polyaryl ether ketone resin composition of the present invention can be used in a wide range of applications, including electronic component applications such as connectors, coils, sensors, LED lamps, sockets, resistors, relay cases, small switches, coil bobbins, capacitors, variable capacitor cases, optical pickups, oscillators, various terminal boards, transformers, plugs, printed circuit boards, tuners, speakers, microphones, headphones, small motors, magnetic head bases, power modules, semiconductors, liquid crystal, FDD carriages, FDD chassis, motor brush holders, parabolic antennas, and computer-related parts; electrical equipment component applications such as generators, electric motors, transformers, current transformers, voltage regulators, rectifiers, inverters, relays, power contacts, switches, circuit breakers, knife switches, other-pole rods, and electrical component cabinets; VTR parts, television parts, irons, hair dryers, rice cooker parts, microwave oven parts, audio parts, audio / visual equipment parts such as audio / laser discs (registered trademark), compact discs, and DVDs; lighting parts, refrigerator parts, air conditioner parts, typewriter parts, word processor parts, and other home and office electrical appliance parts; Computer-related parts, telephone-related parts, facsimile-related parts, copier-related parts, cleaning tools, motor parts, lighters, typewriters and other machine-related parts, microscopes, binoculars, cameras, watches and other optical equipment, precision machinery-related parts, alternator terminals, alternator connectors, IC regulators, light dimmer potentiometer bases, exhaust gas valves and other valves, fuel-related, exhaust and intake pipes, air intake nozzle snorkels, intake manifolds, fuel pumps, engine coolant joints, carburetor main bodies, carburetor spacers, exhaust gas sensors, coolant sensors, oil temperature sensors, brake pad wear sensors, throttle position sensors, crankshaft position sensors, air flow meters, brake pad wear sensors, air conditioner thermostat bases, heating hot air flow control valves, radiator motor brush holders, water pump impellers, turbine vanes, wiper motor-related parts, distributors, starter switches, starter relays,They can be used in a wide range of applications, including transmission wire harnesses, windshield washer nozzles, air conditioner panel switch boards, fuel-related electromagnetic valve coils, fuse connectors, horn terminals, electrical component insulation plates, step motor rotors, lamp sockets, lamp reflectors, lamp housings, brake pistons, solenoid bobbins, engine oil filters, ignition device cases, and other automotive and vehicle-related parts, as well as various aerospace applications. EXAMPLES
[0066] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. Various resins, compounds, etc. used in each example and comparative example are shown below.
[0067] <(A) Polyaryl ether ketone> (A-1) Polyether ether ketone (Victrex (registered trademark) 90G, melting point: 343°C) (A-2) Polyether ketone ketone ("KEPSTAN (registered trademark)" 7002 manufactured by ARKEMA, melting point: 332°C).
[0068] <Polyphenylene sulfide> (Reference example 1) In a 70-liter autoclave equipped with a stirrer and a bottom plug valve, 8.27 kg (70.00 mol) of 47.5% sodium hydrosulfide, 2.94 kg (70.63 mol) of 96% sodium hydroxide, 11.45 kg (115.50 mol) of N-methyl-2-pyrrolidone (NMP), 1.89 kg (23.1 mol) of sodium acetate, and 5.50 kg of ion-exchanged water were charged, and the mixture was gradually heated to 245°C over about 3 hours while passing nitrogen through it at normal pressure. After distilling out 9.77 kg of water and 0.28 kg of NMP, the reaction vessel was cooled to 200°C. The amount of water remaining in the system per mole of the charged amount of alkali metal sulfide was 1.06 mol, including the water consumed in the hydrolysis of NMP. The amount of hydrogen sulfide scattered was 0.02 mol per mole of the charged amount of alkali metal sulfide.
[0069] After cooling the reaction vessel to 200°C, 10.42 kg (70.86 mol) of p-dichlorobenzene and 9.37 kg (94.50 mol) of NMP were added, the reaction vessel was sealed under nitrogen gas, and the temperature was raised from 200°C to 270°C at a rate of 0.6°C / min while stirring at 240 rpm, and the reaction was carried out at 270°C for 140 minutes. Then, 2.40 kg (133 mol) of water was injected while cooling from 270°C to 250°C over 15 minutes. Then, the mixture was gradually cooled from 250°C to 220°C over 75 minutes, and then quenched to near room temperature, and the contents were removed.
[0070] The contents were diluted with about 35 liters of NMP, stirred at 85°C for 30 minutes as a slurry, and filtered through an 80 mesh wire mesh (opening 0.175 mm) to obtain a solid. The obtained solid was washed and filtered with about 35 liters of NMP in the same manner. The obtained solid was added to 70 liters of ion-exchanged water, stirred at 70°C for 30 minutes, and then filtered through an 80 mesh wire mesh to recover the solid. This operation was repeated three times in total. The obtained solid and 32 g of acetic acid were added to 70 liters of ion-exchanged water, stirred at 70°C for 30 minutes, and then filtered through an 80 mesh wire mesh. The obtained solid was further added to 70 liters of ion-exchanged water, stirred at 70°C for 30 minutes, and then filtered through an 80 mesh wire mesh to recover the solid. The solid thus obtained was dried at 120°C under a nitrogen stream to obtain a dried polyphenylene sulfide resin. The mass average molecular weight was 48600 and the melting point was 280°C.
[0071] <(B) Transition metal compound> (B-1) Nickel(II) formate dihydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (B-2) Nickel (II) acetate tetrahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (B-3) Nickel(II) iodide hexahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (B-4) Copper(II) formate tetrahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (B-5) A 3 mass% aqueous solution of nickel (II) formate dihydrate.
[0072] <(C) Alkali metal compounds> (C-1) Anhydrous trisodium phosphate (manufactured by Taihei Chemical Industry Co., Ltd.) (C-2) Anhydrous potassium carbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.).
[0073] <(D) Amine Compound> (D-1) 4,4'-Diaminodiphenyl ether (Tokyo Chemical Industry Co., Ltd., vapor pressure at 300°C: 0.02 atm).
[0074] <(E) Fibrous filler> (E-1) Carbon fiber "TORAYCA (registered trademark)" cut fiber TV14-006 (manufactured by Toray Industries, Inc.) (E-2) Discontinuous carbon fiber mat Toray Industries, Inc.'s "TORAYCA (registered trademark)" T700S-12k carbon fiber chopped yarn cut to a length of 20 mm was introduced into a carding device, and the resulting web was cross-lapped to a weight of 100 g / m 2 The carbon fiber sheet thus obtained was placed in a press and pressed at a pressure of 20 MPa for 5 seconds to obtain a discontinuous carbon fiber mat.
[0075] (E-3) Carbon fiber bundle (Toray Industries, Inc. "TORAYCA (registered trademark)" T700S-12k) <Method of producing polyaryl ether ketone resin composition> Of the raw materials shown in each Example and Comparative Example, the raw materials except for (E-1) carbon fiber were dry-blended according to the composition shown in the table, and fed from the main feeder of a twin-screw extruder (TEX30α manufactured by Japan Steel Works, Ltd.), and (E-1) carbon fiber was fed from a side feeder (installed at a position 0.35 from the upstream side when the total length of the screw is taken as 1.0), and melt-kneaded at a cylinder temperature of 360°C (300°C in Comparative Example 3 and Comparative Example 8) and a screw rotation speed of 200 rpm. The gut discharged from the die was immediately cooled in a water bath, pelletized by a strand cutter, and vacuum dried at 160°C (120°C in Comparative Example 3 and Comparative Example 8) for 12 hours.
[0076] <Method for producing discontinuous fiber reinforced resin substrate impregnated with polyaryl ether ketone resin composition> Of the raw materials shown in Example 14 and Comparative Example 9 in Table 3, the raw materials except for (E-2) discontinuous carbon fiber mat were dry blended in the composition shown in the table, charged into a hopper of a single-screw extruder heated to 380°C, melt-kneaded, and then extruded from a film die into a film having a thickness of 100 μm.
[0077] (E-2) The winding direction of the discontinuous carbon fiber mat was set to 0°, and 12 discontinuous fiber mats were laminated so as to be (0° / 90° / 0° / 90° / 0° / 90°)s. The polyaryletherketone resin composition film was laminated in the laminated discontinuous carbon fiber mat so that the mass ratio of the carbon fiber and the polyaryletherketone resin composition film was 50:50. The whole was sandwiched between stainless steel plates, preheated at 380°C for 90 seconds, and then hot pressed at 370°C for 180 seconds while applying a pressure of 2.0 MPa. The mixture was then cooled to 50°C under pressure to obtain a discontinuous fiber reinforced resin substrate with a thickness of 2 mm.
[0078] <Method for producing continuous fiber reinforced resin substrate impregnated with polyaryl ether ketone resin composition> Among the raw materials shown in Examples 15 to 17 and Comparative Example 10 in Table 3, the raw materials except for (E-3) carbon fiber bundle were dry-blended in the composition shown in the table, and charged into the hopper of a single-screw extruder heated to 380°C. After melt-kneading, the gut discharged from the die was immediately cooled in a water bath, pelletized by a strand cutter, and vacuum-dried at 160°C for 12 hours. Sixteen bobbins wound with (E-3) carbon fiber bundles were prepared, and the carbon fiber bundles were continuously fed from each bobbin through a yarn guide. The continuously fed carbon fiber bundles were impregnated with the resin composition pellets obtained by the above-mentioned method, which were supplied in a fixed amount from a filled feeder, in an impregnation die heated to 380°C. The carbon fibers impregnated with the resin composition in the impregnation die were continuously drawn out from the nozzle of the impregnation die using a take-up roll at a drawing speed of 1 m / min. The drawn carbon fiber bundles passed through a cooling roll to cool and solidify the resin composition, and were wound up on a winder as a continuous fiber-reinforced resin substrate. The thickness of the obtained continuous fiber reinforced resin substrate was 0.08 mm, the width was 50 mm, the reinforcing fibers were aligned in one direction, and the volume content was 60%. Six continuous fiber reinforced resin substrates with a thickness of 0.08 mm were stacked in the same direction and pressed at a pressure of 15 bar for 20 minutes in a press machine heated to 380°C to obtain a laminate of continuous fiber reinforced resin substrates with a thickness of 0.45 mm.
[0079] <Method for evaluating polyaryl ether ketone resin composition> The evaluation methods used in each of the examples and comparative examples will be described below.
[0080] (1) Transition metal content in polyaryl ether ketone resin composition The polyaryl ether ketone resin composition pellets were incinerated, and the incinerated product was heated and decomposed with sulfuric acid and hydrofluoric acid in a sealed container. The constant volume liquid obtained by dissolving the incinerated product in aqua regia was measured by an ICP-MS (inductively coupled plasma mass spectrometer: ELEMENT manufactured by Thermoquest).
[0081] (2) Complete decomposition temperature of transition metal compounds (B) Approximately 10 mg of the transition metal compound alone was weighed out and, using a thermogravimetric analyzer (TGA7 manufactured by PerkinElmer), it was held at 50°C for 1 minute under a nitrogen stream, and then heated from 50°C to 500°C at a heating rate of 10°C / min, and the mass loss was measured when the mass at 50°C was taken as 100%.
[0082] As an example, the results of thermogravimetric analysis of nickel (II) formate dihydrate (B-1) under the above conditions are shown in FIG. 1. The horizontal axis represents temperature T (°C), and the vertical axis represents mass fraction X (%). In the thermogravimetric analysis of nickel (II) formate dihydrate, the dihydrate, which corresponds to 19.5% by mass calculated from the molecular weight, is first evaporated (reference number 1 in FIG. 1), and then formic acid, which corresponds to 48.8% by mass, is evaporated (reference number 2 in FIG. 1). The complete decomposition temperature is defined as the temperature at which the mass reduction rate reaches 90% of the mass of the compound components excluding the transition metal of the transition metal compound. The portion of nickel (II) formate dihydrate excluding the mass of nickel is 68.3% by mass, so 90% of that is 61% by mass. Therefore, the temperature at which a mass reduction of 61.3% by mass is observed is the complete decomposition temperature of nickel (II) formate dihydrate. From FIG. 1, the complete decomposition temperature of nickel (II) formate dihydrate is 260°C.
[0083] (3) Melt viscosity measurement before and after heating The polyaryl ether ketone resin composition pellets were freeze-pulverized / vacuum-dried and used as a sample for measuring melt viscosity before heating. The vacuum drying conditions were 160°C (120°C for Comparative Example 3 and Comparative Example 8) for 12 hours. In addition, about 50 mg of the freeze-pulverized / vacuum-dried sample was piled flatly on a 25mm x 7mm x 7mm micro aluminum dish (manufactured by Alpha Purchase) to a depth of about 300μm, and heated in an electric furnace under air at the melting point of the resin (A) + 70°C for 50 minutes, and the sample after heating was freeze-pulverized / vacuum-dried and used as a sample for measuring melt viscosity after heating. The closer the melt viscosity retention rate before and after heating is to 100%, the more excellent the thermal stability is. The melt viscosity measurement conditions are as follows.
[0084] Apparatus: Rheometer (Anton Paar Physica MCR501) Atmosphere: Nitrogen flow Measurement temperature: (A) resin melting point + 70℃ Angular frequency: 6.28rad / sec Sample size: 0.7g Melt viscosity: Complex viscosity after 5 minutes residence under the above conditions.
[0085] (4) Tensile properties before and after heating The polyaryl ether ketone resin composition pellets were freeze-pulverized / vacuum-dried, and injection-molded into ISO527-2-5A standard dumbbells using a small injection molding machine (Thermo Fisher Scientific, HaakeMiniJetPro) under conditions of a cylinder temperature of 380°C (Comparative Example 3 and Comparative Example 8: 350°C) and a mold temperature of 170°C (Comparative Example 3 and Comparative Example 8: 120°C), to obtain molded products for tensile tests before heating. In addition, about 50 mg of the freeze-pulverized / vacuum-dried sample was piled flatly on a 25mm x 7mm x 7mm micro aluminum dish (Alpha Purchase) to a depth of about 300μm, and heated in an electric furnace under air at the melting point of the resin (A) + 70°C for 50 minutes, and the sample after heating was freeze-pulverized / vacuum-dried and molded under the above molding conditions to obtain molded products for tensile tests after heating. The closer the tensile strength retention rate and tensile breaking elongation retention rate before and after heating are to 100%, the more excellent the thermal stability is. The tensile test conditions are as follows:
[0086] Equipment: Universal mechanical testing machine (Shimadzu Autograph AG-20kNX) Atmosphere: 23℃×50%RH Chuck distance: 50mm Distance between gauge lines: 20mm Pulling speed: 5mm / min.
[0087] (5) Welding test The discontinuous fiber-reinforced resin substrate obtained by the above manufacturing method was cut to dimensions of 300 mm × 400 mm × 2 mm, preheated until the temperature at the center of the substrate reached 400°C, and then placed on a press platen heated to 240°C. Pressurized at 10 MPa for 30 seconds, the substrate was stamped to obtain a fiber-reinforced resin molded body, which was then used for welding.
[0088] The same type of fiber-reinforced resin molded body (length 100 mm, width 25 mm, thickness 2 mm) was stacked as shown in Figure 2, and welded by vibration welding by applying a surface pressure of 1.6 MPa to an area 25 mm wide and with a welding allowance of 12.5 mm.
[0089] (6) Tensile test of welded body It was measured by a lap shear test (shear test) in accordance with JIS K6851. The materials are pulled in opposite directions to apply a shear load, and the tensile strength is measured when the joint breaks or deforms by a specified amount (e.g., interfacial fracture) and the bond strength can be quantitatively evaluated.
[0090] (7) Formability The laminate of the continuous fiber reinforced resin substrate obtained by the above manufacturing method is cut to a thickness of 0.45 mm, a width of 13 mm, and a length of 125 mm. Using a press machine (SA303 manufactured by Tester Sangyo) adjusted to 260 ° C, a laminate 6 preheated until the substrate center temperature reaches 420 ° C is placed between a mold consisting of an upper mold 4 and a lower mold 5 having an uneven shape as shown in FIG. 3, and maintained at a pressure of 1.0 MPa for 5 minutes. The mold is transferred to a press machine (SA303 manufactured by Tester Sangyo) adjusted to 30 ° C and cooled, and a molded product deformed along the shape of the mold is obtained. The depth 3 of the uneven part of this molded product is measured with a vernier caliper. Next, a silicone resin is applied to one of the molds having the uneven shape, and the resin is left in an atmosphere of 23 ° C for 24 hours to harden, and the depth of the uneven shape made of the silicone resin is measured with a vernier caliper. The transfer rate was calculated by dividing the depth of the unevenness of the rectangular molded product by the depth of the unevenness of the silicone resin. A transfer rate of 0.9 or more was rated A, 0.8 or more but less than 0.9 was rated B, and less than 0.8 was rated C.
[0091] (Examples 1 to 3, Reference Examples 4 to 6, Examples 7 to 12, Reference Example 13)
[0092] [Table 1-1]
[0093] [Table 1-2]
[0094] [Table 2]
[0095] A comparison of Examples 1 to 13 and Comparative Examples 1 to 8 shows that by blending a specific amount of a transition metal compound with a polyaryl ether ketone resin, the resin has excellent thermal stability and mechanical properties.
[0096] A comparison of Example 2 with Examples 4 and 5 shows that when the complete decomposition temperature of the nickel compound is below the melting point of the polyaryletherketone, the thermal stability and mechanical properties are excellent, and when it is 300° C. or lower, they are even more excellent.
[0097] A comparison between Example 2 and Example 6 shows that the nickel compound is more excellent in thermal stability and mechanical properties than the copper compound.
[0098] A comparison between Example 2 and Example 7 shows that the transition metal compound added as an aqueous solution has better thermal stability and mechanical properties than the transition metal compound added as a solid. This is believed to be because the transition metal compound is finely dispersed in the polyaryletherketone resin composition.
[0099] A comparison of Examples 2 and 8 shows that the mechanical properties are improved by adding a polyamine.
[0100] (Examples 14 to 17, Comparative Examples 9 and 10)
[0101] [Table 3]
[0102] Comparison of Example 14 and Comparative Example 9 shows that blending a specific amount of a transition metal compound in a polyaryl ether ketone resin results in excellent weld strength. This is believed to be because oxidation degradation of the surface of the discontinuous fiber reinforced resin substrate was suppressed.
[0103] A comparison of Examples 15 to 17 and Comparative Example 10 reveals that blending a specific amount of a transition metal compound into a polyaryl ether ketone resin results in excellent formability. This is believed to be because thickening due to oxidative degradation of the continuous fiber reinforced resin substrate was suppressed. [Industrial Applicability]
[0104] The polyaryl ether ketone resin composition of the present invention can be molded by any method such as injection molding, compression molding, extrusion molding, etc., which are generally known. The polyaryl ether ketone resin composition of the present invention can be processed into various electric and electronic parts, automobile parts, aircraft parts, machine parts, etc., taking advantage of its excellent thermal stability and mechanical properties. In addition, the obtained molded products can be used as fibers for clothing and industrial materials, and films for packaging and magnetic recording. Furthermore, by using the composition as a molded product in combination with a fibrous filler, it is expected to contribute to improving fuel efficiency and reducing greenhouse gas emissions by further reducing the weight, especially in automobile and aerospace applications. [Explanation of symbols]
[0105] 1: Hydrate desorption 2: Elimination of formic acid 3:Depth 4: On the mold 5: Under the mold 6: Laminate
Claims
1. A polyaryl ether ketone resin composition comprising (A) polyaryl ether ketone and (B) a transition metal compound, wherein the transition metal content is 0.001 part by mass or more and 4 parts by mass or less per 100 parts by mass of the (A) polyaryl ether ketone, the (B) transition metal compound is a compound of Group 10 elements of the periodic table, and the (B) transition metal compound has a complete decomposition temperature of 25° C. or more and 300° C. or less.
2. The polyaryl ether ketone resin composition according to claim 1, wherein the complete decomposition temperature of the transition metal compound (B) is equal to or lower than the melting point of the polyaryl ether ketone (A).
3. The polyaryl ether ketone resin composition according to claim 1 or 2, comprising 0.01 parts by mass or more and 5 parts by mass or less of the polyamine (D) per 100 parts by mass of the polyaryl ether ketone (A).
4. The polyaryl ether ketone resin composition according to any one of claims 1 to 3, comprising 10 parts by mass or more and 400 parts by mass or less of the fibrous filler (E) per 100 parts by mass of the polyaryl ether ketone (A).
5. A fiber-reinforced resin substrate obtained by impregnating a continuous (E) fibrous filler or a reinforcing fiber substrate in which a discontinuous (E) fibrous filler is dispersed with the polyaryl ether ketone resin composition according to any one of claims 1 to 3.
6. A molded article obtained by molding the polyaryl ether ketone resin composition according to any one of claims 1 to 4, or the fiber-reinforced resin substrate according to claim 5.
Citation Information
Patent Citations
Special poly(ether-ether-ketone) material used for valves
CN103319876A
Aromatic polyetherketone resin molding material
JP1989066266A
Stabilized polyphenylene ether-polyamide composition
JP1989163262A
Injection-moldable blend of poly (ether ketone) and polyamide-imide
JP1990227458A
Thermoplastic resin composition
JP1991292369A